Minyak Atsiri Biji Pala (Myristica Fragrans Houtt) Terbukti Menurunkan Intensitas Nyeri Sendi di Kota Ambon - Lameky, Vernando Yanry; Nivaan, Goldy Valendria; Akollo, Isak Roberth; Tasijawa, Oci (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Joint pain is a symptom that arises due to diseases such as osteoarthritis, arthritis urica or rheumatoid arthritis. Currently, some people in Ambon City lack the awareness to regularly check the health of their joints and bones. They do not realize that if joint pain is ignored continuously, it will lead to chronic disease and even death. Non-pharmacological treatment is one option, one of which is using nutmeg essential oil (Myristica fragrans houtt) which is the result of the nutmeg tree which is needed in various industries such as the pharmaceutical, food and beverage industries. The aim of this research was to determine the effect of nutmeg essential oil (Myristica fragrans houtt) on reducing the intensity of joint pain in the community in the Waihoka Community Health Center working area. This study implemented a one group pretest-posttest design, involving 15 patients with joint pain who were selected using a purposive sampling technique. Pain levels before and after treatment were measured using a numerical rating scale. Next, a comparative analysis of pain was carried out between before and after treatment using the Wicoxon test. The results of the analysis showed that the p value was 0.000, so it was interpreted that there was a significant difference in pain levels between before and after being given nutmeg essential oil. It was concluded that nutmeg essential oil was effective in reducing joint pain in people in the Waihoka Health Center working area, Ambon.Keywords: nutmeg; Myristica fragrans houtt; joint pain; essential oil ABSTRAK Nyeri sendi merupakan suatu gejala yang timbul karena adanya penyakit seperti osteoarthritis, arthritis urica atau rheumatoid arthritis. Saat ini sebagian masyarakat di Kota Ambon kurang memiliki kesadaran untuk memeriksakan secara rutin kesehatan sendi dan tulang mereka. Mereka tidak menyadari bahwa nyeri sendi yang didiamkan terus menerus akan menimbulkan penyakit kronis hingga kematian. Perawatan non farmakologi merupakan salah satu pilihan, yang salah satunya adalah menggunakan minyak atsiri biji pala (Myristica fragrans houtt) yang merupakan hasil dari pohon pala yang sangat dibutuhkan dalam berbagai industri seperti industri farmasi, makanan dan minuman. Tujuan penelitian ini adalah untuk mengetahui pengaruh minyak atsiri biji pala (Myristica fragrans houtt) terhadap penurunan intensitas nyeri sendi pada masyarakat di wilayah kerja Puskesmas Waihoka. Penelitian ini menerapkan rancangan one group pretest-posttest, yang melibatkan 15 pasien dengna nyeri sendi yang dipilih menggunakan teknik purposive sampling. Tingkat nyeri sebelum dan sesudah perlakuan diukur menggunakan numerik rating scale. Selanjutnya dilakukan analisis perbandingan nyeri antara sebelum dan sesudah perlakuan menggunakan uji Wicoxon. Hasil analisis menunjukkan bahwa nilai p adalah 0,000, ehingga ditafsirkan bahwa ada perbedaan tingkat nyeri secara bermakna antara sebelum dan sesudah diberikan minyak atsiri biji pala. Disimpulkan bahwa minyak atsiri biji pala efektif untuk menurunkan nyeri sendi pada masyarakat di wilayah kerja Puskesmas Waihoka, Ambon.Kata kunci: biji pala; Myristica fragrans houtt; nyeri sendi; minyak atsiri